ACTIVE POWER LOSS REDUCTION & STATIC VOLTAGE STABILITY MARGIN ENHANCEMENT BY AERIFORM NEBULA ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, Aeriform Nebula Algorithm (ANA) has been used for solving the optimal reactive power dispatch problem. Aeriform Nebula Algorithm (ANA) is stirred from the deeds of cloud. ANA imitate the creation behavior, modify behavior and expand deeds of cloud. The projected Aeriform Nebula Algorithm (ANA) has been tested on standard IEEE 30 bus test system and simulation results shows clearly about the superior performance of the proposed Aeriform Nebula Algorithm (ANA) in reducing the real power loss and voltage stability has been enhanced.